Human Resource Management Perspective of Al Maqasid Al Šar'iyyah in Islamic Education Institutions - Misbakul Munir, Muhammad; Saputra, Refki (Journal of World Science, 2022)
Introduction: The management of human resources in Islam has a noble goal, which is to keep them away from darkness, corruption, ignorance and misery towards true and eternal goodness and success (Al Falah). This is the great goal that Islam conveys to every human being. Of course, to achieve this noble goal requires a holistic concept and management. The purpose of this study is to describe human resource management from the perspective of LPI Al Maqasid Al Šar'iyyah, namely the perspective of hifzud din, difzun nafs/haya/al 'Ir?, hifzul 'aql, hifzun nasal, hifzul mal. Method: The writing method is a literature study with primary data from journals and books. Result: The result of this paper is that the perspective of Al Maqasid Al Šar'iyyah (Hifzud Din, Hifzun Nafs/hayat/Al 'Ird, Hifzul 'Aql, Hifzun Nasl, Hifzul Mal) can provide a holistic formula regarding the management of human resource management in Islamic educational institutions so that creating superior human resources that will have a positive impact on the progress and quality of Islamic educational institutions. Conclusion: Human resource management from an Islamic perspective must be based on the principles and functions of Islamic management. Al Maqasid Al Šar'iyyat's perspective on HRM in order to achieve a big goal, namely Al Falah (good in this world and the hereafter). Implementation from the perspective of Al Maqasid Al Šar'iyyat's on HRM at LPI is a management formulation to realize credible, professional, and quality HR towards an advanced, quality, and competitive LPI.